Digital marketing and customer loyalty strategies in service companies. A systematic review between 2016-2022. (LACCEI, 2024)
Through the exploration of 29 scientific research articles published in the world during the periods 2016-2022, the objective of the work is to Evaluate whether digital marketing influences customer loyalty strategies in service companies. Likewise, the present study is based on an inductive method starting from the specific to the general using the systematic review methodology as well as an analysis and synthesis methodology that includes the review of scientific article bases, repositories, specialized journals detection, query extraction, collection and integration of data. From the result of the investigation, it is concluded that digital media have a great reception in the service category, due to its great reach with its public objective and the proximity that it projects when in contact with its environment, in this way it can communicate a clear and direct message in a few minutes and instantly to achieve a call to action to build customer loyalty from the first contact with the company, and having a strategy is essential for the development of promotional activities, communication and attraction of new customers.